Psikoterapi islam dan implikasinya dalam pendidikan karakter pada masa modernisasi - Salmarita; Muhiddinur Kama (Program Studi Akuntansi IKOPIN, 2022)
The background of writing this thesis is that character education during this modernization period is very important because of the influence of very rapid technological developments that make teenagers tend to be addicted to gedget adar or notthat they are influenced by outside cultures that are inappropriate to apply so that it has a bad impact on morals, mental and physical. spiritual. The purpose of the study was to determine the concept of Islamic psychotherapy and itsinteraction in character education during the modernization period based on the work of Hamdani Bakran Adzaky.The type of research used is library research or library research in which the collection of data and information from various written or monumental documents that have relevance to the object of research that aims to solve a problem is basically focused on a critical and in-depth study of library materials. relevant.The results showed that: 1) Islamic psychotherapy is a healing or treatment with benefits or guiding the Qur'an and sunnah in life so as to display good morals and spirituality as human leaders on earth. Psychotherapy methods used are Takhalli, Tahalli and Tajalli. 2) The implication of Islamic psychotherapy in character education during the modernization period is the involvement to guide and educate it with the Hamdani Bakran Ad-Dzaky psychotherapy method, namely Takhalli, Tahalli and Tajalli. The three methods are complements in character education, with the religious concept offered in Islamic psychotherapy that can have a positive impact on the advancement of a golden, moral and dignified generation.